Exercise-Induced Improvements in Postprandial Glucose Response Are Blunted by Pre-Exercise Hyperglycemia: A Randomized Crossover Trial in Healthy Individuals - Carter, Steven; Solomon, Thomas P. J. (Frontiers in Endocrinology, 2020)
Background Exercise improves glycemic control but the magnitude, and in some cases, the direction of this effect is variable. Ambient hyperglycemia has been implicated in this exercise response heterogeneity. The current study investigated whether pre-exercise hyperglycemia directly impacts the effect of exercise on glycemic control. Methods Twelve healthy normal glucose-tolerant males completed four trials in a randomized, crossover design. Each trial consisted of 24-h pre-intervention monitoring, a 7-h intervention, and 24-h post-intervention monitoring. Glycemic control was measured throughout the study by continuous glucose monitoring. The four interventions were no exercise (CON) or 45 min of cycling exercise (70%HRmax) preceded by 3.5 h of either normoglycemia (NG-Ex), steady-state hyperglycemia induced by constant glucose infusion (HG-Ex) or fluctuating glycemia induced by repeated glucose bolus infusions (FG-Ex). Results Physical activity and diet were similar between trials, and energy expenditure during exercise was matched between exercise trials (all P > 0.05). Mean glucose during the 3.5 h ± infusion period was higher in HG-Ex (mean ± SEM; 7.2 ± 0.4 mmol/L) and FG-Ex (7.3 ± 0.3 mmol/L) compared to CON (4.8 ± 0.2 mmol/L) and NG-Ex (5.0 ± 0.2 mmol/L) trials (P < 0.01). Glycemic variability was greatest in FG-Ex (P < 0.01). Following the interventions, the postprandial glucose response (iAUC) was reduced by exercise in NG-Ex compared to CON (321.1 ± 38.6 vs. 445.5 ± 49.7 mmol/L.8h, P < 0.05, d=0.81). This benefit was blunted when exercise was preceded by steady-state (HG-Ex, 425.3 ± 45.7 mmol/L.8h) and fluctuating (FG-Ex, 465.5 ± 39.3 mmol/L.8h) hyperglycemia (both P > 0.05 vs. CON). Conclusion Pre-exercise hyperglycemia blunted the glucoregulatory benefits of acute exercise upon postprandial glucose response, suggesting that exposure to hyperglycemia contributes to exercise response heterogeneity. Clinical Trial Registration ClinicalTrials.gov, identifier NCT03284216.